Since the constant has been moved to the left side, you can move on to the next step which is adding (b/2)² to both sides of the equation.
h² + 14h + (14/2)² = -31 + (14/2)²
Simplify the parenthesis and exponent.
h² + 14h + 7² = -31 + 7²
h² + 14h + 49 = -31 + 49
h² + 14h + 49 = 18
Factor the expression of the left.
(h + 7)(h + 7) = 18
Take the square root of both sides.
√(h + 7)(h + 7) = ± √9 • 2
(h + 7) = ± 3√2
h + 7 = ± 3√2
Subtract 7 from both sides.
You solutions are:
h = -7 + 3√2 → -2.7573 → -2.76
h = -7 - 3√2 → -11.2426 → -11.24
Answer:
See explanation below
Step-by-step explanation:
The best explanation is noticing that in order to get from the point R (12, 1) to the point Q (7, 4) we move 5 units to the left and 3 units up. And to go from point Q (7, 4) to point P (2, 7) we do exactly the same: move 5 units to the left and 3 units up. That means that these points are all connected via the same rate of change: - 3/5, which is in fact the slope of the line the three points belong to.
Answer:
-17/5
Step-by-step explanation:
Multiply ten to everything to get
6x-1= x+2-20
Simplify to 5x= -17
Solve to get x = -17/5
Answer:
Step-by-step explanation:
So you should know. Can you give us a better picture?
Y=5 just flip the question sort of